EKSPLORASI BAKTERI PELARUT FOSFAT DI LAHAN GAMBUT BERENG BENGKEL, KALIMANTAN TENGAH (Phosphate Solubilizing Bacteria Eksploration in Peatland Bereng Bengkel, Central Kalimantan): Krestina, W.1) - Admin journal (AgriPeat, 2018)
ABSTRACTThe high availability of organic compounds in peatlands is stored capital and can be converted intoelements by soil microbe. The high organic content causes nutrients in the soil cannot be directlyutilized by plants. Phosphate solubilizing bacteriaare soil bacteria that capableofsolubilizingphosphate, turns it into an available form in the soil. The aims of this research are todiscover the existence of a phosphate solubilizing bacteriagenus and obtain potential pure isolatesfrom Bereng Bengkel peatland, Central Kalimantan. Bacteria isolation usingselective mediaPikovskaya with pour plate method. The isolation results are five phosphate solvent bacterialisolates (BPF1, BPF2, BPF3, BPF4, BPF5) which form hallozone. Based on the characterizationresults refering to the Bergey's Manual of Determinative of Microorganism through macroscopicobservation, microscopic observation and physiological testing. BPF1 and BPF5 isolates were thegenus Rhodococcusgenus, BPF2 isolates were theRhizobiumgenus, BPF3 isolates were theMicorococcusgenus, BPF4 isolates were the SerratiagenusKeywords: Phosphate solubilizing bacteria, peatland, soil bacteria